USING MODERN NONACRYLIC BASIC MATERIAL IN CLINICAL PROSTHETIC DENTISTRY - V.S. Kuz; V.N. Dvornyk; G.M. Kuz (Український стоматологічний альманах)
Background. The effectiveness of orthopedic treatment of edentulous patients depends on the properties of the basic materials. The main group of materials for manufacturing of such structures is acrylic plastics of thermal polymerization. However, many years of experience in the use of plastics have revealed a number of shortcomings. One of the main shortcomings is insufficient functional durability of prostheses, and as a consequence the fragility of acrylic constructions. At present, more and more dentists use nonacrylic thermoplastics, which can improve the functional quality of full removable dentures, as well as, avoid the above disadvantages of acrylic basic plastic.